Debt Stocks, Debt Flows and the Balance of Payments. (International Monetary Fund, 1994)
This report focuses on the ways in which stock data enter into the analysis of the flow of external resources between creditor and debtor countries. It describes key terms and the various debt classification systems; outlines methodologies for reconciling differences in debt stocks and debt flows; compares and contrasts the debt and debt-related data systems of the IMF, the OECD, and the World Bank; provides two case studies on data analysis problems and examples of debt restructuring; and outlines the conclusions of the International Working Group on External Debt Statistics.